BioMet-Think Aid : a learning package to enhance student practical experience in basic biochemistry and metabolism - Nurul Farhana Jufri; Farah Wahida Ibrahim; Nor Farah Mohamad Fauzi; Nor Fadilah Rajab; Asmah Hamid; Mazlyzam Abdul Latif (Penerbit Universiti Kebangsaan Malaysia, 2021)
Basic Biochemistry and Metabolism is a compulsory course offered to the 1st year students of the Biomedical Science Program, Faculty of Health Sciences, Universiti Kebangsaan Malaysia. Understanding the theories and procedures concerning each practical is very crucial. All the techniques introduced are clinical biochemistry-based tests that are widely used in diagnostic lab. Previously, students were only given a practical manual which was disseminated days earlier followed by a short briefing before each practicals session. The students, however, could not fully grasp the content of the manual given, resulting in experimental errors, inaccurate findings and chemical wastage. Also, the instruments involvedwere sometimes mishandled resulting in an increased risk of damage or untoward accidents. To overcome these problems, Biokimia Metabolisme Think Aid (BioMet-Think Aid) learning package was introduced to enhance students’ understanding when performing the practical sessions. The BioMet-Think Aid package consists of a step-by-step video-based practical demonstration, reference posters for expected results and quizzes for assessing students’ understanding. This package was distributed to the students to serve as a preparatory package for the practical sessions. The feedback showed that the BioMet-Think Aid package resulted in increased students’ understanding (100%), adequate practical execution time (90%) and confidence in performing the experiments (100%). Positive feedbacks were also received from relevant teaching and technical staffs. Overall, the BioMet-Think Aid package serves as a catalyst to enhance students’ experience in learning Basic Biochemistry and Metabolism and it will be continued to be implemented to the future enrolled students.